1997
DOI: 10.1073/pnas.94.23.12401
|View full text |Cite
|
Sign up to set email alerts
|

Bok is a pro-apoptotic Bcl-2 protein with restricted expression in reproductive tissues and heterodimerizes with selective anti-apoptotic Bcl-2 family members

Abstract: In the intracellular death program, heteroand homodimerization of different anti-and pro-apoptotic Bcl-2-related proteins are critical in the determination of cell fate. From a rat ovarian fusion cDNA library, we isolated a new pro-apoptotic Bcl-2 gene, Bcl-2-related ovarian killer (Bok). Bok had conserved Bcl-2 homology (BH) domains 1, 2, and 3 and a C-terminal transmembrane region present in other Bcl-2 proteins, but lacked the BH4 domain found only in anti-apoptotic Bcl-2 proteins. In the yeast two-hybrid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
301
2
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(321 citation statements)
references
References 48 publications
11
301
2
7
Order By: Relevance
“…The need for caspase activity was also reported in the induction of apoptosis by transient overexpression of some other anti-apoptotic members of the Bcl-2 family of proteins, for example Bid (Wang et al, 1996), Bak and Bik (Orth and Dixit, 1997) and Bok (Hsu et al, 1997).…”
Section: Bcl-x S -Induced Cell Death Requires Caspase Activitymentioning
confidence: 75%
See 1 more Smart Citation
“…The need for caspase activity was also reported in the induction of apoptosis by transient overexpression of some other anti-apoptotic members of the Bcl-2 family of proteins, for example Bid (Wang et al, 1996), Bak and Bik (Orth and Dixit, 1997) and Bok (Hsu et al, 1997).…”
Section: Bcl-x S -Induced Cell Death Requires Caspase Activitymentioning
confidence: 75%
“…The anti-apoptotic members of the Bcl-2 family include Bcl-2, Bcl-x L , Bcl-W, Mcl-1, B¯1/ A1, E1B 19k, Epstein-Barr virus BHRF1, and Caenorhabditis elegans Ced-9. Pro-apoptotic members include Bax, Bak, Bad, Bik, Bid, Bim, Hrk, Bok/Mtd, Blk and Bcl-x S (for review see Hegde et al, 1998;Hsu et al, 1997;Kelekar and Thompson, 1998;O'Connor et al, 1998;Strasser et al, 1997 and references therein). The homology between members of the Bcl-2 family resides mainly within four conserved domains, designated Bcl-2 homology (BH) domains BH1, BH2, BH3 and BH4.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 However, more should be done to investigate cell death regulation when these mice are stressed in various ways. Expression of the bok gene is limited to testis, ovary, and uterus in mice, 43 though expression of the human ortholog of this gene may be more widespread, including liver and kidney. 44 Genotoxic injury experiments using bokÀ/À mice did not reveal a requirement for bok for cell death in ovaries or other organs.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Bok expression was first reported to be restricted to reproductive tissues. 16 However, we have recently shown that BOK can be detected in most tissues, albeit in several at only relatively low levels. 20 The BOK protein was found to localize to the mitochondria, the ER as well as to the nucleus.…”
mentioning
confidence: 99%
“…2,[10][11][12][13][14][15] BOK (BCL-2-related ovarian killer) was identified in a yeast two-hybrid screen using MCL-1 as bait and was shown to selectively interact with MCL-1 and BFL-1/A1 but not with BCL-2 or BCL-X L . 16,17 Among the BCL-2 family members, BOK shows the highest evolutionary conservation. 18,19 Bok expression was first reported to be restricted to reproductive tissues.…”
mentioning
confidence: 99%